PERAN LEMBAGA PEMBIAYAAN SYARIAH DALAM MENINGKATKAN KEMANDIRIAN EKONOMI MASYARAKAT DESA - Lailatul Vitriyah, Nurul; Ristiawati, Rika; Sari, Emilda; Sigit Adi Nugraha, Mohammad; Silviawati, Selly (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Improving the economic independence of rural communities is one of the main goals of national economic development and requires the support of inclusive and just financial institutions. This study aims to analyze the role of Islamic financing institutions in enhancing the economic independence of village communities in District X through the provision of Sharia-compliant financing access and business assistance for micro-entrepreneurs. This research employs a qualitative approach with a case study method, using in-depth interviews, observations, and documentation involving micro-entrepreneurs, clients, and stakeholders of Islamic financing institutions. The findings indicate that Islamic financing institutions play a significant role in expanding access to capital, improving knowledge of Islamic financial management, and strengthening the capacity of micro-enterprises, as reflected in increased income and economic independence among most respondents. Nevertheless, limitations in financial literacy and understanding of Sharia principles are still found among rural communities, indicating the need for stronger educational programs and continuous mentoring. These results confirm that optimizing the role of Islamic financing institutions has great potential to support sustainable and equitable rural economic development.